Analisis Hukum Responsif terhadap Pembatasan Usia Pernikahan terhadap Hak Perempuan di Indonesia - Nilna Niamatin; Iza Hanifuddin; Rohmah Maulidia (Journal of Economics, Law, and Humanities, 2023)
This descriptive qualitative study with a literature study approach aims to explore the "marriage age limit" in perspective and categorization in the typology of responsive law. The main material object is "limiting the age of marriage" as a legal norm following legislation (Law 1 of 1974 Ps. 7 Paragraphs 1 and 2). The formal object is ideas, ideas, and arguments that support or reject the idea of the article a quo. The analysis uses a responsive legal theory approach, an epistemological and axiological study of the review of the limitation of the age of marriage as a statutory norm applicable in Indonesia. The results show that: 1) The situation of child marriage because it is allowed to marry at the age of 16 (Article 7 paragraph (1) of Law 1 of 1974) results in the guarantee of women's constitutional rights being violated. These violations include the right to education, health, and growth and development, guaranteed protection by the 1945 Constitution. Applying legal norms needs to balance the protection of children and human rights. 2) The scope of the case includes the right to make life choices and the right to the growth and development of children—the synergy of all parties to educate the community about the adverse effects of early marriage. Provide access to quality health and education services for children so that they can grow and develop properly and ensure the law can effectively increase the prevention of child marriage cases.